ANALISIS ARAH LULUSAN DALAM KEBIJAKAN PENDIDIKAN ISLAM PADA ERA ORDE BARU (1990–2000) - Muhammad Azmi Auf; Ahmad Arifi, Ahmad Arifi (IAI Sunan Giri Trenggalek, 2025)
This study analyzes the orientation of Islamic education graduates in Indonesia during the late New Order and early Reform periods (1990–2000). It departs from the contrast between the dominant state perspective, which viewed Islamic education as an instrument for political stability and national development, and a critical perspective that considers education as a space for liberation and social awareness. The research aims to describe the state policies on Islamic education during the New Order, examine the shifts in graduate orientation during the crisis and Reform transition, and explore institutional strengthening and intellectual development after 2000. This study employs a qualitative research design with an interpretive critical approach, grounded in Paulo Freire’s theory of critical consciousness and Antonio Gramsci’s concept of hegemony, applied to analyze policy documents, curricula, and Islamic education archives. The findings reveal that Islamic education under the New Order was directed toward producing bureaucratic and ideologically loyal graduates, while in the Reform era it shifted toward institutional autonomy and intellectual professionalism. The study concludes that the orientation of Islamic education graduates reflects the dynamic relationship between political power and the transformation of social consciousness. This research contributes to the study of Islamic education politics through a historical–critical and ideological analytical approach.